Cooling Load Capacity Analysis in The Departure Apron Corridor Area at Supadio Airport Using the Cooling Load Temperature Difference Method (CLTD) - Mury Rahadi; Doddy Irawan; Eko Julianto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
This study presents an evaluation of the cooling load capacity in the departure apron corridor area at Supadio International Airport using the Cooling Load Temperature Difference (CLTD) method. The objective of the research is to assess whether the current air conditioning (AC) is adequate to meet thermal comfort requirements in a tropical climate characterized by high humidity and strong solar radiation. A detailed field survey was conducted at Gate 3, a glass-dominated corridor that experiences significant heat gain from solar exposure. Empirical data including temperature profiles, material properties, occupancy levels, and equipment specifications were collected over a two-week period using digital instruments. Using the CLTD method, the heat contributions from walls, roof, glass surfaces, occupants, lighting, and air infiltration were quantified. The results revealed that the installed AC (2 PK) only delivers about  of the required cooling load, with the total load estimated at 66,448 BTU/hr. The dominant sources of thermal gain include the roof and east-facing glass panels. The study recommends AC resizing, glass shading implementation, and improved insulation to enhance energy efficiency. This research contributes practical insights for HVAC optimization in airport infrastructure within hot-humid climates.